Systematic Review on the Importance of Gut Microbiota in the Regulation of Type 2 Diabetes Through Physical Activity and Exercise - Luis Muguerza-Rodríguez; Alba Mier; Jesus G. Ponce-González; Cristina Casals; Juan Corral-Pérez (Current Issues in Molecular Biology, 2025)
Type 2 diabetes (T2D) is a major global health issue, influenced by sedentary behavior and obesity. Emerging evidence implicates the gut microbiota in T2D pathophysiology through effects on glucose metabolism, inflammation, and insulin sensitivity. This systematic review included eleven studies, six observational and five interventional, examining the relationship between physical activity, exercise, and gut microbiota in individuals with or at risk of T2D. Observational studies associated low physical activity and high sedentary time with reduced α-diversity and increased abundance of potentially harmful bacteria. Interventional studies showed that structured exercise, including moderate-intensity and sprint interval training, increased beneficial bacteria such as Faecalibacterium, Veillonella, Lachnospira, and Bifidobacterium, linked to anti-inflammatory effects and improved metabolic profiles. However, overall microbial diversity often remained unchanged unless combined with dietary modifications. Exercise also reduced levels of trimethylamine N-oxide, a metabolite linked to cardiovascular risk. Despite increases in butyrate-producing taxa, most studies did not report significant short-term changes in short-chain fatty acid levels, highlighting the complex interaction between microbiota and host metabolism. These findings support physical activity and exercise as modifiable factors that can influence gut microbiota composition, potentially contributing to improved metabolic regulation and better management of T2D.